Anthocyanin의 Delphinidin이 MDA-MB-231 유방암세포에 미치는 영향 - 장혜연(Hye-Yeon Jang); 이송희(Song-Hee Lee); 안인정(In-Jung An); 이해님(Hae-Nim Lee); 김혜리(Hye-Ri Kim); 박영석(Young-Seok Park); 박병권(Byung-Kwon Park); 김병수(Byeong-Soo Kim); 김상기(Sang-Ki Kim); 조성대(Sung-Dae Cho); 남정석(Jeong-Seok Nam); 최창순(Chang-Sun Choi); et al. (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2014)
This research showed that delphinidin, an anthocyanin present in blueberry, induced apoptosis in MDA-MB-231 breast cancer cells as well as mediated anti-cancer effects in vivo. As a result, growth of cancer cells as assessed by MTT assay decreased in a concentration-dependent manner. Chromatin condensation by DAPI staining significantly increased in a concentration-dependent manner, indicating apoptosis. The level of p53-protein increased while those of anti-apoptotic molecules (Bcl-2, p-$GSK3β$) decreased in the western blot. Tumor size decreased in cells treated with 10 mg/kg of delphinidin compared with the control group in vivo. Cell apoptosis assessed by TUNEL assay significantly increased, and tumor inhibitory effect was confirmed. Therefore, delphinidin can be developed for cancer preventive medicine due to its growth inhibitory effects and induction of apoptosis in human breast cancer cells. 본 연구에서는 블루베리에 포함된 anthocyanin 중 delphinidin이 인간 유래의 MDA-MB-231 유방암세포의 성장을 억제시키고 apoptosis를 유발하는지 살펴보고 in vivo 실험에서도 항암효과가 나타나는지 확인하였다. 그 결과 cell viability를 보기 위한 MTT assay에서는 농도 의존적으로 암세포의 성장을 억제시켰으며, apoptosis의 확인을 위한 DAPI stain에서 농도 의존적으로 chromatin condensation이 유의적으로 증가하는 것을 확인하였다. 또한 western blot에서 암 억제 유전자인 p53 단백질이 증가하였고, anti-apoptotic 분자인 Bcl-2 단백질과 p-$GSK3β$ 단백질은 감소하였다. In vivo 실험에서는 대조군과 비교해 10 mg/kg delphinidin을 투여한 군에서 종양의 크기가 감소하였으며, TUNEL assay를 통해 apoptosis 세포 또한 통계학적으로 유의적인 증가가 관찰되어 종양 억제 효과를 확인하였다. 이상의 결과들로 볼 때, MDA-MB-231 유방암세포에서 delphinidin은 암세포의 증식을 억제시키고, apoptosis를 유발시키는 효과를 보이므로 암 예방제나 치료제로 개발될 수 있을 것으로 사료된다.